Food security and community development in the Pacific: Case studies from Fiji - Vunibola, Suliasi; Leweniqila, Ilisoni (https://crawford.anu.edu.au/rmap/devnet/dev-bulletin.php, 2021)
This paper considers the role of bola vakavanua (the Fijian way of life) in two indigenous Fijian communities, Saroni ¹ and Bucalevu,² in helping rural villages achieve food security. Traditional mechanisms such as so/esolevaki (cultural capital through collective work), together with monthly community work structures in place, can help households achieve food security. Revitalising these traditional mechanisms, encouraging wider use of them, and establishing legal frameworks for protecting traditional food security could have widespread benefits. (¹ Saroni village is in Dogotuki district, Macuata; ² Bucalevu village is in Nakorotubu district in west Viti Levu)
Published with permission of the Development Bulletin.
Keywords: Food security; Community development; Traditional farming; Fiji